The first record of Physalis angulata L. (Solanaceae) for the flora of Libya - Mahklouf, Mohammed H. (Biodiversity: Research and Conservation, 2019)
Physalis angulata has been discovered and recorded for the first time in the flora of Libya. This species was collected from the Bilash′har region belonging to the city of Tajura, about 20 km east of Tripoli. P. angulata is easily identified by its small yellow flowers without central dark spots in the center, and by pedulus globose berry enclosed within an inflated bladdery fruiting calyx. Detailed descriptions, photographs, habitat and ecology are provided for easy identification, and to facilitate further identification of this species and to warrant its future detection.